Unusual case of suspected recurrent scarlet fever in a UK serviceman. Issue 2 (13th April 2018) - Phillips, Rachel; Martin-Bates, A J; Withnall, R
Abstract : The UK prevalence of scarlet fever, a Group A streptococcal infection, is increasing. We present an unusual case of suspected recurrent scarlet fever in a member of the UK Armed Forces. Treatments, occupational implication and public health measures to mitigate the risk of disease spread.